Effect of long-term fertiliser regimes and weather on spring barley yields in sandy soil in North-East Germany. Issue 13 (9th November 2020) - Thai, Thi Huyen; Bellingrath-Kimura, Sonoko Dorothea; Hoffmann, Carsten; Barkusky, Dietmar
ABSTRACT: The interaction effects of different fertilisation regimes and weather variability on crop yield is a challenge that requires long-term investigation. Therefore, yield data for spring barley (SB) in an agricultural long-term field experiment, established in 1963 in Müncheberg, northeast Germany, were analysed to reveal the effects of 21 fertiliser regimes and different weather conditions on SB yields. SB yields were significantly affected by fertilisation regimes (11%), annual weather conditions (55%) and their interaction effect (8%). Mineral N fertilization decreased overall yield variability across seasons as compared to no fertilization and organic fertilization regimes showed higher yield variability. A suitable combined application of mineral nitrogen and organic fertiliser was found to be an effective way to produce higher SB yields than the application of either mineral nitrogen or organic fertiliser alone. A Bayesian linear regression model showed total precipitation during the growing season (April–July) positively affected on SB yields when high mineral N was supplied. At the early growth stage, a precipitation rate (March) and temperature (April or sowing day) negatively affected on SB yield.